2011
DOI: 10.1523/jneurosci.0567-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Astroglial Dicer Causes Non-Cell-Autonomous Neuronal Dysfunction and Degeneration

Abstract: The endoribonuclease, Dicer, is indispensible for generating the majority of mature microRNAs (miRNAs), which are posttranscriptional regulators of gene expression involved in a wide range of developmental and pathological processes in mammalian central nervous system. While functions of Dicer-dependent miRNA pathways in neurons and oligodendrocytes have been extensively investigated, little is known about the role of Dicer in astrocytes. Here we report the effect of Cre-loxP mediated conditional deletion of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 53 publications
6
131
0
Order By: Relevance
“…shown in numerous studies to have reliably astrocyte-specific expression (22)(23)(24)(25). Consistent with this, we observed deletion of Ifnar on cortical and cerebellar astrocytes, with intact expression of the receptor on nonastrocytic cells.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…shown in numerous studies to have reliably astrocyte-specific expression (22)(23)(24)(25). Consistent with this, we observed deletion of Ifnar on cortical and cerebellar astrocytes, with intact expression of the receptor on nonastrocytic cells.…”
Section: Methodssupporting
confidence: 91%
“…Given the findings from our own studies demonstrating that IFNAR signaling in astrocytes enhances in vitro BBB integrity in response to WNV (4), we used Ifnar fl/fl Gfap-Cre mice, in which IFNAR signaling was abrogated in glial fibrillary acidic protein-expressing (GFAP-expressing) astrocytes, to evaluate the contribution of astrocyte IFNAR signaling to WNV pathogenesis and disease. For these studies, we chose the Gfap-Cre line 77.6, which was previously shown to exhibit a Cre expression that is more specific to astrocytes than to other GfapCre lines (22)(23)(24)(25). We also used an established in vitro BBB model to examine how forebrain versus hindbrain astrocytes differentially regulate barrier function.…”
Section: Cerebellum (961%) Analysis Of Ifnar Expression On Map2mentioning
confidence: 99%
“…Otherwise, this would not be the first time that changes to genes in astrocytes at an epigenetic level are seen to influence normal neuronal function. For instance, Tao and colleagues showed that selectively knocking-out Dicer in astrocytes leads to neuronal dysfunction and degeneration 62 . Thus far BEGAIN has been investigated and localized in nuclei and synapses of neurons 56 , but there is no information on its relation to astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Dicer is an RNase III essential to the cleavage of pre-miRNA to mature miRNA. The deletion of Dicer in the neural system typically leads to neuronal dysfunction, neurodegeneration, macular degeneration, epilepsy seizure and cognitive deficits [53][54][55][56][57]. The loss of Dicer appears specific to TLE patients with HS and cause a failure of miRNA biogenesis, which further gives rise to degenerative changes in cortex and hippocampal morphology that have been observed in human epilepsy [54].…”
Section: Micrornas Expression Regulation In Epilepsymentioning
confidence: 99%